Early Sex Differentiation of Climbing Perch (Anabas testudineus Bloch.): A Pathway to Feminization - Hidayat, Rahmat; Carman, Odang; Alimuddin, Alimuddin (Universitas Airlangga, 2024)
The phenomenon of sexual dimorphism in climbing perch, which shows that female fish grow faster than males, underlies the development of mono-sex culture. Female mono-sex culture is more applicable for farmers by crossing neo-male fish with normal females. The timing of sexual differentiation in climbing perch is still unknown. It is very useful in sex reversal procedures to produce neo-male climbing perch. This study revealed the time and status of climbing perch sexual differentiation. Ten samples of climbing perch from the spawning of five pairs of parents were taken from the nursery pond at 10–29 days post-hatching (dph). Samples were prepared through a histology preparation procedure. Observations of the structure and characteristics of the gonads were carried out using a light microscope and analyzed histologically. The results indicated that gonad samples aged 10, 11, 12, 13, 15, and 16 dph showed primordial germ cells surrounded by somatic tissue forming genital ridges and mitotic division. Meanwhile, the gonads begin to differentiate as ovaries found at 18 dph with the presence of oogonia and ovarian cavities. Gonads aged 20–21 dph increasingly showed single oogonia cells (size 20–37.5 µm), germ cell cysts, genital ridges, oocytes undergoing the vitellogenesis process, perinucleolar oocytes, and the formation of the ovarian cavity. Sex differentiation of climbing perch was predicted from 18–21 dph. This conclusion underlies that the sex reversal procedure in climbing perch must be carried out before 18 dph.